(untitled) (Journal of Engineering, 2022)
Dry gas is considered one of the most environmentally friendly sources of energy. As a result, developing an efficient strategy for storing this gas has become essential. In this work, MOF-199 was synthesized and characterized in order to investigate the MOF-199 in dry gas adsorption using a built-in volumetric system (methane, ethane, and propane from Basrah gas company). The MOF-199 (metal organic framework) was synthesized using the solvothermal method at 373K for 24h, and then it was characterized. The dry gas adsorption on MOF-199 was studied under various conditions (adsorbent dosage, contact time, temperature, and pressure). The isothermal adsorption of the dry gas had been studied on MOF-199 using two types of models: Freundlich and Langmuir. The results of the isothermal adsorption shown corresponded to the Freundlich model with a correlation coefficient (R²) of 0.9426. Also, the rate of adsorption kinetic of the first and second-order was studied, and the results showed that the reaction rate was second-order.